Expand your horizons with the diverse and informative answers found on IDNLearn.com. Our platform is designed to provide accurate and comprehensive answers to any questions you may have.
Sagot :
Let's complete the table step by step.
1. To find [tex]\( x \)[/tex] when [tex]\( g(x) = 7 \)[/tex]:
Given the function [tex]\( g(x) = -4x - 1 \)[/tex], set [tex]\( g(x) = 7 \)[/tex]:
[tex]\[ 7 = -4x - 1 \][/tex]
Solving for [tex]\( x \)[/tex]:
[tex]\[ 7 + 1 = -4x \implies 8 = -4x \implies x = \frac{8}{-4} \implies x = -2 \][/tex]
2. To find [tex]\( g(x) \)[/tex] when [tex]\( x = 0 \)[/tex]:
Substitute [tex]\( x = 0 \)[/tex] into [tex]\( g(x) = -4x - 1 \)[/tex]:
[tex]\[ g(0) = -4(0) - 1 = 0 - 1 = -1 \][/tex]
3. To find [tex]\( x \)[/tex] when [tex]\( g(x) = -13 \)[/tex]:
Given the function [tex]\( g(x) = -4x - 1 \)[/tex], set [tex]\( g(x) = -13 \)[/tex]:
[tex]\[ -13 = -4x - 1 \][/tex]
Solving for [tex]\( x \)[/tex]:
[tex]\[ -13 + 1 = -4x \implies -12 = -4x \implies x = \frac{-12}{-4} \implies x = 3 \][/tex]
4. To find [tex]\( g(x) \)[/tex] when [tex]\( x = -1 \)[/tex]:
Substitute [tex]\( x = -1 \)[/tex] into [tex]\( g(x) = -4x - 1 \)[/tex]:
[tex]\[ g(-1) = -4(-1) - 1 = 4 - 1 = 3 \][/tex]
Now, we can complete the table as follows:
[tex]\[ \begin{tabular}{|c|c|} \hline $x$ & $g(x)$ \\ \hline -2 & 7 \\ \hline 0 & -1 \\ \hline 3 & -13 \\ \hline -1 & 3 \\ \hline \end{tabular} \][/tex]
1. To find [tex]\( x \)[/tex] when [tex]\( g(x) = 7 \)[/tex]:
Given the function [tex]\( g(x) = -4x - 1 \)[/tex], set [tex]\( g(x) = 7 \)[/tex]:
[tex]\[ 7 = -4x - 1 \][/tex]
Solving for [tex]\( x \)[/tex]:
[tex]\[ 7 + 1 = -4x \implies 8 = -4x \implies x = \frac{8}{-4} \implies x = -2 \][/tex]
2. To find [tex]\( g(x) \)[/tex] when [tex]\( x = 0 \)[/tex]:
Substitute [tex]\( x = 0 \)[/tex] into [tex]\( g(x) = -4x - 1 \)[/tex]:
[tex]\[ g(0) = -4(0) - 1 = 0 - 1 = -1 \][/tex]
3. To find [tex]\( x \)[/tex] when [tex]\( g(x) = -13 \)[/tex]:
Given the function [tex]\( g(x) = -4x - 1 \)[/tex], set [tex]\( g(x) = -13 \)[/tex]:
[tex]\[ -13 = -4x - 1 \][/tex]
Solving for [tex]\( x \)[/tex]:
[tex]\[ -13 + 1 = -4x \implies -12 = -4x \implies x = \frac{-12}{-4} \implies x = 3 \][/tex]
4. To find [tex]\( g(x) \)[/tex] when [tex]\( x = -1 \)[/tex]:
Substitute [tex]\( x = -1 \)[/tex] into [tex]\( g(x) = -4x - 1 \)[/tex]:
[tex]\[ g(-1) = -4(-1) - 1 = 4 - 1 = 3 \][/tex]
Now, we can complete the table as follows:
[tex]\[ \begin{tabular}{|c|c|} \hline $x$ & $g(x)$ \\ \hline -2 & 7 \\ \hline 0 & -1 \\ \hline 3 & -13 \\ \hline -1 & 3 \\ \hline \end{tabular} \][/tex]
Thank you for being part of this discussion. Keep exploring, asking questions, and sharing your insights with the community. Together, we can find the best solutions. Discover the answers you need at IDNLearn.com. Thanks for visiting, and come back soon for more valuable insights.